2016
DOI: 10.1111/nph.13878
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and metabolome of synthetic Solanum autotetraploids reveal key genomic stress events following polyploidization

Abstract: SummaryPolyploids are generally classified as autopolyploids, derived from a single species, and allopolyploids, arising from interspecific hybridization. The former represent ideal materials with which to study the consequences of genome doubling and ascertain whether there are molecular and functional rules operating following polyploidization events.To investigate whether the effects of autopolyploidization are common to different species, or if species-specific or stochastic events are prevalent, we perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 94 publications
4
37
0
Order By: Relevance
“…The synthetic polyploids showed the same profile observed for the natural polyploids (Viccini et al, 2014). The analysis of the metabolism of autopolyploid plants suggests that polyploidy may cause both qualitative and quantitative changes in the essential oil, due to changes in the mechanisms that regulate its biosynthesis (Fasano et al, 2016;Iannicelli et al, 2020). Vieira et al (2016) suggested that synthesis of citral, geraniol and other compounds prevailed in diploids, while non-oxygenated monoterpenes were the major ones in polyploids of Citrus limonia.…”
Section: Discussionmentioning
confidence: 52%
“…The synthetic polyploids showed the same profile observed for the natural polyploids (Viccini et al, 2014). The analysis of the metabolism of autopolyploid plants suggests that polyploidy may cause both qualitative and quantitative changes in the essential oil, due to changes in the mechanisms that regulate its biosynthesis (Fasano et al, 2016;Iannicelli et al, 2020). Vieira et al (2016) suggested that synthesis of citral, geraniol and other compounds prevailed in diploids, while non-oxygenated monoterpenes were the major ones in polyploids of Citrus limonia.…”
Section: Discussionmentioning
confidence: 52%
“…As can be observed, there is a lack of linearity between the increase in genetic material (ploidy level) and the production rate of specialized metabolites in different medicinal and aromatic plants (Iannicelli et al, 2020). Changes in the metabolic profile of autopolyploids were interpreted as being the result of an alteration in the mechanism(s) regulating the biosynthesis of individual compounds (Fasano et al, 2016). Naturally occuring polyploids have been under pressures of the natural selection for a long period of time after polyploidization and therefore differences in metabolite concentration between diploid and polyploid genotypes may be due to selection.…”
Section: Resultsmentioning
confidence: 99%
“…Nonpolar (carotenoids) and semi-polar (phenylpropanoid) analyses were carried out by liquid chromatography coupled to diodearray detector and atmospheric pressure chemical ionizationhigh-resolution mass spectrometry (LC-DAD-APCI-HRMS) or electrospray ionization (LC-DAD-ESI-HRMS), respectively, operating in positive and negative ion modes, as previously described (D'Esposito et al, 2017;Fasano et al, 2016;Su et al, 2015). Identification of carotenoids was performed as reported previously (Liu et al, 2014).…”
Section: Nonpolar and Semi-polar Metabolite Analysesmentioning
confidence: 99%